An Empirical study of the value relevance of accounting information on market price in sub financial sectors in Sri Lanka - Mayadunne, MKMU. (IJRDO - Journal of Business Management, 2017)
The study focuses to analyze the value relevance of accounting information on investor’s decisions. The research objectives are to identify the relationship between value relevance of accounting information and market price and to find out the impact of value relevance of accounting information on investor’s decisions. For this study a sample of 21 banking, finance and insurance companies were used in Colombo Stock Exchange in Sri Lanka over period of 05 years from 2009 to 2013.Market price were used as dependent variable and return on equity , earning yield, net assets value per share, earning per share were used as independent variable. Correlation analysis were used to find out the relationship and impact of independent and dependent variables. The result revealed that return on equity, earning per share and net assets value per share has a positive significant relationship on market price. Further and earning yield has no significant relationship with market price. Moreover finding revealed that the return on equity, earning per share and net assets value per share has significant impact on market price